Control of Black Medic in Strawberry Production - Shaun M. Sharpe; Nathan S. Boyd (EDIS)
Black medic is an annual broadleaf weed that competes with strawberry crops and impedes harvest. This 4-page document describes how to manage black medic in strawberry production. Written by Shaun M. Sharpe and Nathan S. Boyd and published by the UF/IFAS Horticultural Sciences Department, July 2018. http://edis.ifas.ufl.edu/hs1319